SUCCESSFUL ENTREPRENEURS THROUGH EFFECTIVE COMMUNICATION STRATEGIES IN BUSINESS - Debrina Intan Meilani; Candra Aeni (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Success in the world of entrepreneurship is often determined not only by the quality of the product or service offered, but also by an entrepreneur's ability to implement effective communication strategies. The right communication strategy plays an important role in building good relationships with consumers, business partners and all stakeholders. This article examines in depth how effective communication strategies can support the success of an entrepreneur in developing his business. Using the literature study method, this article reviews the basic theories and concepts of business communication, analyzes communication strategies in various business contexts, and the benefits of effective communication in building reputation and business competitiveness. The study results show that entrepreneurs who are able to manage communications strategically have greater potential to achieve success in business.